Immunohistochemistry Essential Elements and Beyond - Kalyuzhny, Alexander E. (Techniques in Life Science and Biomedicine for the Non-Expert, 2016)
Aimed at both beginners and experienced researchers unfamiliar with the technique, this book provides a concise and easy-to-understand guide to using immunohistochemistry. It identifies the proper place and purpose of each component of immunohistochemistry, emphasizes the components that are of critical importance, and explains the logistics of experimental approaches. Understanding the principles of immunohistochemistry allows for the identification and localization of protein targets and is of crucial use in the following experiments: · producing transgenic animals · studying the effects of drug treatments · electrophysiological studies · animal surgery · isolating and differentiating stem cells · super-resolution microscopy Immunohistochemistry for the Non-Expert is aimed at a wide audience, including molecular biologists, pharmacologists, immunologists, chemists, cell biologists, physiologists, and researchers involved with animal anatomy studies.